e-Learning Sebagai Peran Teknologi Informasi Dalam Modernisasi Pendidikan - Gani, Alcianno G. (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2016)
The main form in the development of human resources is education and training. However, when considering the circumstances of geography, socio-economic and cultural diversity of Indonesia, it is clear that it is no longer sufficient when only relying on traditional ways of solving alone. In the global era, as now, agree or not, want or do not want to be associated with the technology, especially information technology. This is because the technology has affected our daily lives. Therefore, we should not be blind to the technology. Many research results indicate that whoever whose late to controls the information, it's too late to precisely obtain opportunities to advance. The developments of the science of information and communication technologies have an impact on various aspects of life, including education. Distance education or can be also referred to as distance learning, have started ogled by the perpetrators of education to be one solution of educational problems above. More precisely began to be a "trend-centers" in our education. Actually, the term has long been echoed even applied by educators and learners in a learning process in this case are mostly done separately outside the classroom. Separately here means between educators and learners are not in the same room even time could be different. Development of Internet technology gives a feel of distance education system that is more open again. Learning system Web-based popular as electronic learning (e-learning), Web-Based Training (WBT) or sometimes called Web-Based Education (WBE), virtual campus, mobile learning (m-learning), etc has been developed extensively. With the situation thus, distance learning or open learning will be pioneers entered the new decade.